If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3t + -9t + -19 = -1 Reorder the terms: -19 + 3t + -9t = -1 Combine like terms: 3t + -9t = -6t -19 + -6t = -1 Solving -19 + -6t = -1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '19' to each side of the equation. -19 + 19 + -6t = -1 + 19 Combine like terms: -19 + 19 = 0 0 + -6t = -1 + 19 -6t = -1 + 19 Combine like terms: -1 + 19 = 18 -6t = 18 Divide each side by '-6'. t = -3 Simplifying t = -3
| 8p-7p=12 | | 13w-12w+2w=18 | | 10u+-2u+13u+-17u=-16 | | 4v-2v+2v-3v=14 | | 15n+n-13n=9 | | j-j+j-j+j=7 | | 2z^3-5z^2-3=0 | | 6g-19g-3g+-9g+10g=9 | | z-z+z=9 | | 14y-13y=8 | | -2x+43=x+16 | | 8n-7n+3n+-19n=2 | | 5x+31=2x+4 | | 2x+x+(x+5)+y=100 | | -2x-23=2x+1 | | 3x+5+y=100 | | 3x+y-5=100 | | 8s+2s=20 | | 19d-15d=16 | | 38-f=-30 | | -x+23=2x+8 | | 3(m+3)+24=69 | | 2x+x+y=100 | | 7x(12/6-2)^2-6 | | h-27/-7=-9 | | 7x+55=3x+23 | | 9(m+1)=54 | | 3(s+22)+10=88 | | -12/r=-3 | | -c^2+c+30=0 | | -3(s+18)=-15 | | 6x+40=2x+4 |